Guidance in Developing Tourism Communication Skills and Character Building for The Mosque Youth Association - Rusmawan, Putu Ngurah; Darmawan, Randhi Nanang; Kanom, Kanom; Setianingsih, Tri (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to help the mosque youth association, which consisted of 20 people as the participants, develop English proficiency in tourism communication and character building. The service method included observation, lectures, participatory approaches, the application of technology, and innovation.Â The evaluation of this service was done by monitoring and analyzing activity progress and achievements and written tests and practicing tests of communication skills and character building, given that the team compared the pre-test and the post-test. From the evaluation at the end of the community services by using post test, showed that almost 90% of the mosque youth participants improved their capability in tourism communication as well as character building. The results of this community service activity could improve the mosque youth's ability to use English and prepare them to interact with the global community.